أثر الحمولة المرجعية للمناهج الغربية في التحديث النقدي لدى أحمد يوسف - مناصري, وفاء (جامعة الوادي - university of Eloued, 2020)
تتأتّى مسألة البحث في النقد الجزائري من فعل التشافع الرؤوي بين ما أفرزته الحركات النقدية في الغرب -أروبيا وأمريكيا- ومدى قابلية الآخر (الناقد الجزائري) للاستجابة والتفاعل مع معطيات الطرح الجديد، وتكيفها نظريا وتطبيقيا مع مقتضيات الحركة الإبداعية وطنيا. الكلمات المفتاحية: النقد الجزائري/ سيميائيات/ التفاعل/ المرجعية/أحمد يوسف Abstract Algerian criticism is the result of an interactive movement between what the European and the American produced in the field of criticism Thus, the research is about the extent of the Algerian critic's response to the other and his ability to adapt this imported data to the national creative product. key words: Algerian criticism / semiotics / interaction / reference / Ahmed Youssef.
مقال
Keywords: لنقد الجزائري/ سيميائيات/ التفاعل/ المرجعية/أحمد يوسف